Should the Government Be Paying Investment Fees on $3 Trillion of Tax-Deferred Retirement Assets? - Landoni, Mattia; Zeldes, Stephen P (Review of Financial Studies, 2025)
Under standard assumptions, individuals and the government are indifferent between traditional tax-deferred retirement accounts and “front-loaded” (Roth) accounts. Adding investment fees to this benchmark, individuals are still indifferent, but the government is not. We show that under weak conditions firms charge equal percent fees under both systems, yielding higher dollar fees under Traditional. We estimate that tax deferral increases demand for asset management services by $3.8 trillion, costing the government $23.4 billion in annual fees. In a general equilibrium differentiated-product model, tax deferral produces a larger asset management industry, higher taxes, and lower social welfare.